2017
DOI: 10.1074/jbc.a112.442384
|View full text |Cite
|
Sign up to set email alerts
|

A cardiac-enriched microRNA, miR-378, blocks cardiac hypertrophy by targeting Ras signaling.

Abstract: This article has been withdrawn by the authors. Lanes 1 and 2 of the actin immunoblot in Fig. 3B were reused in lanes 3 and 4 of the actin immunoblot in Fig. 7C. The ANF immunoblot in Fig. 3B was reused as ANF in Fig. 9F. Control lanes 1 and 2 of the ANF immunoblot in Fig. 8C were duplicated. The Grb2 and GAPDH immunoblots in Fig. 9C were inappropriately manipulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…In addition, reduced miR-378a-3p by flavonoid fisetin inhibited fat accumulation in the liver [30]. In organ fibrosis, miR-378a-3p has been reported to be abundant in cardiomyocytes and miR-378a-3p down-regulation contributes to the development of cardiac fibrosis involving a TGFβ1-dependent paracrine mechanism [16,31]. In this study, we found that miR-378a-3p was down-regulated in CCl 4 -treated rats and activated HSCs.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, reduced miR-378a-3p by flavonoid fisetin inhibited fat accumulation in the liver [30]. In organ fibrosis, miR-378a-3p has been reported to be abundant in cardiomyocytes and miR-378a-3p down-regulation contributes to the development of cardiac fibrosis involving a TGFβ1-dependent paracrine mechanism [16,31]. In this study, we found that miR-378a-3p was down-regulated in CCl 4 -treated rats and activated HSCs.…”
Section: Discussionmentioning
confidence: 58%
“…Specifically, miR-378 expressions were found significantly higher in the serum of humans with alcohol use disorders (Ignacio et al 2015). MiR-378 includes both miR-378-5p and miR-378-3p, which are mature microRNAs derived from a common hairpin RNA precursor expressed from a single non-coding gene (Nagalingam et al 2013). Although neither miR-378-5p nor ALDH2 gene has been previously identified as a target of ethanol exposure, prior studies in ischemia conditions have shown a list of miRNAs that negatively regulate ALDH2 function could be associated with increased cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, high expression of miR-378 can even suppress the cell proliferation and induces apoptosis by targeting BRAF, as observed by Wang et al (13). Although the correlation between miR-378 and MAPK signaling pathway were revealed by substantial evidence, for example, Nagalingam et al emphasized Ras signaling could be one of the main targets of miR-378 in cardiac hypertrophy (14), however, the underlying mechanism of different subtypes of CRC, which correlated with sensitivity to the targeting therapy or regulation of miR-378 still remain unknown.…”
Section: Introductionmentioning
confidence: 96%